2010
DOI: 10.1177/1352458509359924
|View full text |Cite
|
Sign up to set email alerts
|

TI-relaxation time changes over five years in relapsing-remitting multiple sclerosis

Abstract: The pathological effects of multiple sclerosis are not confined to lesions; tissues that appear normal on conventional magnetic resonance imaging scans are also affected, albeit subtly. One imaging technique that has proven sensitive to such effects is T1-relaxation time measurement, with previous work demonstrating abnormalities in normal-appearing white matter and grey matter. In this work we investigated the evolution of T1-relaxation time changes in normal-appearing white matter and grey matter in relapsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
0
30
2
1
Order By: Relevance
“…Therefore, we did 3 Normalized histograms of NAWM for two subjects (solid line and dashed line) at months 0 (black) and 6 (grey) for T 1 and T 2 relxation-derived metrics: a T 1 , b MWF and c GMT 2 . No statistically significant change was observed over time; however, clear intersubject variability exists not observe the larger changes seen by other T 1 -relaxation studies that have shown peak height to decrease from a range of 1.6-7% per year [26,27,41,42]. In particular, previous longitudinal studies of RRMS subjects have found similarly small longitudinal changes in NAWM T 1 mean and peak location.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Therefore, we did 3 Normalized histograms of NAWM for two subjects (solid line and dashed line) at months 0 (black) and 6 (grey) for T 1 and T 2 relxation-derived metrics: a T 1 , b MWF and c GMT 2 . No statistically significant change was observed over time; however, clear intersubject variability exists not observe the larger changes seen by other T 1 -relaxation studies that have shown peak height to decrease from a range of 1.6-7% per year [26,27,41,42]. In particular, previous longitudinal studies of RRMS subjects have found similarly small longitudinal changes in NAWM T 1 mean and peak location.…”
Section: Discussionmentioning
confidence: 65%
“…They did find weak evidence for a decline over time in NAWM T 1 peak height but rejected such findings due to lack of significant difference between patient-control rate of change. In contrast, Parry et al [26] and Papadopoulos et al [27] both found significant decrease in T 1 peak height over 14-22 months in 9 RRMS and 5 secondary progressive MS subjects and 3-5 years in 35 RRMS subjects, respectively. The discrepancy between Parry's findings and Davies as well as ours may be due to the addition of secondary progressive MS (SPMS) subjects in their study.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, with relaxation times of different pathologies overlapping considerably [3][4][5], more complex tissue characterization came into focus, for example, those based on water diffusion, magnetization transfer, and perfusion. It became obvious that the strengths of quantitative or semi-quantitative MR parameter maps lie in the detection of diffuse changes in brain tissues that appeared normal in conventional MRI [6][7][8], best demonstrated in multiple sclerosis patients [2,7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%